Chronic Social Stress Leads to Reduced Gustatory Reward Salience and Effort Valuation in Mice - Kúkel’ová, Diana; Bergamini, Giorgio; Sigrist, Hannes; Seifritz, Erich; Hengerer, Bastian; Pryce, Christopher R. (Frontiers in Behavioral Neuroscience, 2018)
Pathology of reward processing is a major clinical feature of stress-related neuropsychiatric disorders including depression. Several dimensions of reward processing can be impacted, including reward valuation/salience, learning, expectancy and effort valuation. To establish the causal relationships between stress, brain changes, and reward processing pathologies, valid animal models are essential. Here, we present mouse experiments investigating behavioral effects of chronic social stress (CSS) in association learning tests of gustatory reward salience and effort valuation. The reward salience test (RST) comprised Pavlovian pairing of a tone with gustatory reward. The effort valuation test (EVT) comprised operant responding for gustatory reinforcement on a progressive ratio schedule (PRS). All testing was conducted with mice at 100% baseline body weight (BBW). In one experiment, mice underwent 15-day CSS or control handling (CON) and testing was conducted using sucrose pellets. In the RST on days 16–17, CSS mice made fewer feeder responses and had a longer tone response latency, than CON mice. In a shallow EVT on days 19–20, CSS mice attained a lower final ratio than CON mice. In a second CSS experiment, mice underwent CSS or CON and testing was conducted with chocolate pellets and in the presence of standard diet (low effort/low reward). In the RST on days 16–18, CSS mice made fewer feeder responses and had a longer tone response latency, than CON mice. In a steep EVT on days 19–20, CSS and CON mice attained less pellets than in the RST, and CSS mice attained a lower final ratio than CON mice. At day 21, blood levels of glucose and the satiety adipokine leptin were similar in CSS and CON mice. Therefore, CSS leads to consistent reductions in reward salience and effort valuation in tests based on association learning. These reward pathology models are being applied to identify the underlying neurobiology and putative molecular targets for therapeutic pharmacology.